PWM and duty ratio switching of multiple input converters using FPGAs: a digital logic circuit and VHDL hybrid approach - Jiya, Immanuel; Snyman, Wian; Gurusinghe, Nicoloy; Gouws, Rupert (International Journal of Engineering and Technology, 2018)
This paper presents work that addresses the need for the simultaneous switching of the gate signals of controllable switches in multiple input DC-DC converters. A hybrid approach of implementing the gate signal switching using a combination of digital logic circuits and the conventional VHDL is used in this research. This approach reduces the complexity of the gate signal switching of multiple input converters when compared to the conventional methods. A new method of designing the digital logic circuits from the steady state waveforms of the multiple input DC-DC converter is also introduced, the logic circuit was verified in simulation and validated experimentally by implementing it on an FPGA development board. From the experimental results presented, the switching of the multiple input converter was achieved with the possibility of using any type of system controller without affecting the operation of the switching signals. A dead time of up to 400 nanoseconds was achieved between the switching signals and ultimately, the new method of designing the digital logic circuit of the converter operation from the steady state waveform was validated.Â